1994
DOI: 10.1111/j.1432-1033.1994.00617.x
|View full text |Cite
|
Sign up to set email alerts
|

Transport of β‐alanine and biosynthesis of carnosine by skeletal muscle cells in primary culture

Abstract: Uptake of p-alanine and synthesis of carnosine (P-alanyl-histidine) could be demonstrated in primary cell cultures derived from embryonic chick pectoral muscle. Concomitant with the morphological changes, cessation of cell division and the induction of creatine kinase, a rapid increase in the rate of p-alanine uptake and also in the rate of carnosine synthesis could be observed. The uptake of p-alanine is sodium and chloride dependent and obeys Michaelis-Menten kinetics with K, values of about 40 pM that are e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 22 publications
0
43
0
2
Order By: Relevance
“…All the currently known ␤-alanine-synthesizing enzymes have low expression levels in muscles, where the demand for ␤-alanine is great; accordingly, it is generally considered that the intramuscular ␤-alanine is transported from elsewhere to make carnosine (13). A study with chicken embryonic muscle cell culture indicated that a ␤-amino acid transporter is present in the cells (45); hence the sarcoplasmic ␤-alanine delivery is the rate-limiting factor for muscle carnosine synthesis. ␤-Alanine supplementation has been exploited to boost the blood ␤-alanine concentration, drive the carnosine synthesis in muscles, and improve muscle performance (46).…”
Section: Discussionmentioning
confidence: 99%
“…All the currently known ␤-alanine-synthesizing enzymes have low expression levels in muscles, where the demand for ␤-alanine is great; accordingly, it is generally considered that the intramuscular ␤-alanine is transported from elsewhere to make carnosine (13). A study with chicken embryonic muscle cell culture indicated that a ␤-amino acid transporter is present in the cells (45); hence the sarcoplasmic ␤-alanine delivery is the rate-limiting factor for muscle carnosine synthesis. ␤-Alanine supplementation has been exploited to boost the blood ␤-alanine concentration, drive the carnosine synthesis in muscles, and improve muscle performance (46).…”
Section: Discussionmentioning
confidence: 99%
“…Carnosine synthetase (EC 6.3.2.11), whose activity is 98% cytosolic (Harding and O'Fallon, 1979), is an enzyme characterized by a broad substrate specificity, capable of synthesizing different aminoacyl-histidine dipeptides (e.g., carnosine, homocarnosine, anserine; Winnick and Winnick, 1959;Kalyankar and Meister, 1959;Ng and Marshall, 1978;Horinishi et al, 1978). The synthesis has been demonstrated to occur in different tissues, including muscle (Bakardjiev and Bauer, 1994;Bauer and Schulz, 1994) and brain (Horinishi et al, 1978). A carnosinase (EC 3.4.13.3) and an homocarnosinase responsible for the degradation of these compounds have also been identified in different tissues (Rosemberg, 1960;Harding and Margolis, 1976;Lenney, 1976;Lenney et al, 1977;Ng et al, 1977;Ng and Marshall, 1978;Harding and O'Fallon, 1979;Margolis et al, 1983;Margolis and Grillo, 1984b).…”
Section: Carnosine and Carnosine-related Dipeptidesmentioning
confidence: 99%
“…Several lines of evidence suggest that carnosine synthetase is not saturated with its substrate in physiological conditions and that the immediate precursor β-alanine may play a role in regulating tissue carnosine levels (Margolis et al, 1985). In cell cultures, biosynthesis of carnosine has been demonstrated to occur in muscle cells and in glial cells (Bauer et al, 1982;Bakardjiev and Bauer, 1994;Hoffmann et al, 1996;Bakardjiev, 1997). By contrast, no significant synthesis of homocarnosine was described, probably due to the fact that glial cells rapidly degrade γ-aminobutyric acid, a precursor of homocarnosine.…”
Section: Carnosine Synthesis and Uptakementioning
confidence: 99%
“…β-alanine can be obtained through the hydrolysis of dipeptides extracted from dietary meat or fish and through the degradation of uracil in the liver [10]. Bakardjiev and Bauer [11] have shown that the transsarcolemmal transport of one molecule of β-alanine requires two sodium ions and one chloride ion.…”
Section: Metabolic Pathways Of Carnosinementioning
confidence: 99%